Mechanisms of interferon-gamma (IFN-y)-induced hyperpermeability changes in human umbilical vein endothelial cells - Ng, Chin Theng (2017)
Endothelial dysfunction, characterized by increased endothelial permeability, is the initiating step in the pathogenesis of vascular diseases such as atherosclerosis. Interferon-gamma (IFN-γ), a pro-inflammatory cytokine, has been reported to impair the endothelial barrier and thus, increases vascular permeability. However, the mechanism by which IFN-γ disrupts the endothelial barrier has never been clarified. Therefore, this study aimed to evaluate the underlying mechanisms of IFN-γ-induced hyperpermeability changes using human umbilical vein endothelial cells (HUVECs). HUVECs were used as a model system to study permeability changes because inflammatory events are commonly occurs in postcapillary venules in vivo. As a preliminary step, the HUVECs viability was determined using MTT and ATP assays. Permeability changes were assessed using in vitro permeability assay kits. Localization of F-actin, caldesmon, β-catenin and vascular endothelial cadherin (VE-cadherin) was studied using confocal microscope. Total protein expressions of β-catenin, VE-cadherin, F- /G-actin, p38 MAP kinase, phosphorylated-p38 MAP kinase (p-p38 MAP kinase), caldesmon and phosphorylated-caldesmon (p-caldesmon) were performed using Western blot analysis. Protein expressions of β-catenin and VE-cadherin in different cell compartments were studied using subcellular protein fractionation kit. The interactions of caldesmon to actin and myosin were studied using a co-immunoprecipitation assay. The levels of nitric oxide (NO) and cyclic guanosine monophosphate (cGMP) were detected using Griess assay and enzyme-linked immunosorbent assay (ELISA), respectively. The present study showed that IFN-γ increased HUVECs permeability in a biphasic manner. The hyperpermeability changes may be associated with actin remodeling and alteration of adherens junctions (AJs). In the first phase, IFN-γ caused cell rounding and peripheral actin bands, which may be regulated by caldesmon phosphorylation and dissociation of actin with caldesmon. Besides, IFN-γ induced discontinuous AJs formation without altering the AJs expression level. On the other hand, the second phase of increased permeability involves cell elongation and stress fiber formation, which may be regulated by F-actin hyperpolymerization. Besides, IFN-γ induced linearized AJs, and downregulated the AJs expression level in membrane and cytoskeleton fractions. The results showed that IFN-γ activated p38 MAP kinase in the signaling pathway. However, p38 MAP kinase only regulated the first phase of IFN-γ-mediated increased permeability, and F-actin remodeling. Besides, NO partially regulated the IFN-γ-induced HUVECs hyperpermeability and this was independently of cGMP. In summary, the study enhances the current knowledge on the mechanism of IFN-γ in inducing endothelial dysfunction. The mechanisms underlie IFN-γ-mediated HUVECs hyperpermeability may involve F-actin remodeling and alteration of AJs structure and expression, suggesting that actin cytoskeleton and AJs may serve as the potential therapeutic targets for prevention of the endothelial dysfunction mediated by IFN-γ. The p38 MAP kinase and NO are not the primary regulator for the regulation of IFN-γ-induced endothelial barrier impairment.